Teachers’ perception toward the impact of platform used in online learning communication in the eastern Indonesia - Maru, Mister Gidion; Tamowangkay, Fransisca Priskila; Pelenkahu, Noldy; Wuntu, Ceisy (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
This study aims at revealing teachers’ perception toward the online platforms such as Google Classroom and WhatsApp used during the Covid-19 pandemic. This research applies qualitative descriptive method and involves English teachers in Bitung, a port and growing city in North Sulawesi in Eastern Indonesian, as the research respondents. The data are obtained from semi-structured interview. The data are then analyzed in the frame of Miles and Huberman triangulation. The findings of the research show that the teachers tend to use Google Classroom and WhatsApp as their means of managing the learning practices and communication during the pandemic. As online platforms. These are regarded to be effective for teachers to keep in touch with the students and conduct online teaching including sending videos, making a group chat, and having video conference. In addition to having advantage and disadvantages, these online platforms are considered being appropriate to assist the students to conduct their learning from home. Yet, some aspects such as the availability of internet infrastructure and networks seem to be potential hindrances ahead.